2002
DOI: 10.1021/jf020341r
|View full text |Cite
|
Sign up to set email alerts
|

Mousy Off-Flavor of Wine:  Precursors and Biosynthesis of the Causative N-Heterocycles 2-Ethyltetrahydropyridine, 2-Acetyltetrahydropyridine, and 2-Acetyl-1-pyrroline by Lactobacillus hilgardii DSM 20176

Abstract: The N-heterocyclic bases, 2-ethyltetrahydropyridine (1), 2-acetyl-1-pyrroline (2), and 2-acetyltetrahydropyridine (3) are associated with the occurrence of mousy off-flavor in wine. The biosynthesis of these N-heterocycles by the wine lactic acid bacterium, Lactobacillus hilgardii DSM 20176, was studied by high-cell-density incubation in combination with a minimal chemically defined N-heterocycle assay medium. The key components of the defined N-heterocycle assay medium included D-fructose, ethanol, L-lysine, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 25 publications
4
71
1
Order By: Relevance
“…The availability of the precursor's lysine and ornithine has a significant impact on the ability of LAB to produce these compounds (Costello & Henschke, 2002). Costello & Henschke (2002) also found that the lack of ethanol drastically reduces the ability of L. hilgardii to produce Nheterocycles, whereas elevated concentrations of acetaldehyde sti mulates formation. Lactic acid bacteria differ in their preference for the formation of the different nitrogen heterocyclic compounds.…”
Section: Nitrogen Containing Compoundsmentioning
confidence: 98%
“…The availability of the precursor's lysine and ornithine has a significant impact on the ability of LAB to produce these compounds (Costello & Henschke, 2002). Costello & Henschke (2002) also found that the lack of ethanol drastically reduces the ability of L. hilgardii to produce Nheterocycles, whereas elevated concentrations of acetaldehyde sti mulates formation. Lactic acid bacteria differ in their preference for the formation of the different nitrogen heterocyclic compounds.…”
Section: Nitrogen Containing Compoundsmentioning
confidence: 98%
“…The odour thresholds of ACPY and ACTPY have been determined in water as 0.1 and 1.6 μg/L, respectively. Wines that are found to be spoiled by the mousy taint have been found to contain one or more of the three main compounds: ETPY levels of 2.7-18.7 μg/L, ACPY concentrations up to 7.8 μg/L and ACTPY at concentrations of 4.8-106 μg/L (Costello and Henschke 2002). Costello and Henschke (2002) investigated the biosynthesis of ETPY, ACPY and ACTPY by L. hilgardii DSM 20176.…”
Section: Ornithine/lysinementioning
confidence: 99%
“…It was found that ornithine stimulates the formation of ACPY while lysine stimulates the formation ACTPY. Conversely, ornithine represses the formation of ACTPY while lysine represses the formation of ACPY (Costello and Henschke 2002). Costello et al (2001) found that LAB differ in their ability to produce these compounds.…”
Section: Ornithine/lysinementioning
confidence: 99%
“…Trace experiments with 15 N-proline, 15 N-glycine, and proline-1-13 C indicated that the nitrogen source of 2AP was proline, whereas the carbon source of the acetyl group was not its carboxyl group (Yoshihashi et al 2002). Costello and Henschke (2002) suggested role of ornithine as nitrogen source of 2AP via Putrescine pathway. Intermediate 1-pyrroline could then be subjected to acylation of C-2 position of acyl-CoA derivatives, thus leading to synthesis of 2AP.…”
Section: Substrate Specificity and Activity Of Badh2mentioning
confidence: 97%